1998
DOI: 10.1103/physrevb.58.113
|View full text |Cite
|
Sign up to set email alerts
|

Specific heat of the ternary compoundsUPd2Si2and

Abstract: The specific heat of the single crystals of UPd 2 Si 2 and UNi 2 Si 2 has been studied using the step heating method for the temperature range between 2 and 250 K. Successive phase transitions at high temperatures were observed for both samples, which are consistent with previously reported magnetization and neutron scattering results. No evidence of any phase transition was observed at temperatures below 70 K, which has been previously reported. The Debye temperature and the electronic specific heat coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This value is consistent with previous specific-heat data. 11,15 The transition from the UAF phase to the AF-I phase is also the first-order transition accompanied by a discontinu-ous volume change, ⌬Vϭ3.6ϫ10 Ϫ8 m 3 mol Ϫ1 at T 1 . As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This value is consistent with previous specific-heat data. 11,15 The transition from the UAF phase to the AF-I phase is also the first-order transition accompanied by a discontinu-ous volume change, ⌬Vϭ3.6ϫ10 Ϫ8 m 3 mol Ϫ1 at T 1 . As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 Previous neutron diffraction studies in available magnetic fields applied along the c axis revealed a complex magnetic phase diagram with the splitting of the T 1 phase boundary above 3 T. 1,2,4 The T 2 transition was not seen in the so far published specific heat data. 5 Naturally, a detailed study of the specific heat of UNi 2 Si 2 is highly desirable.…”
mentioning
confidence: 99%
“…The magnetic field-temperature (H-T) phase diagram of this material comprises, except for the paramagnetic phase, three ordered phases, all with magnetic moments along the c axis [10][11][12][13]. In zero field the low temperature phase T < 96.5 K is a simple antiferromagnet (AFI) (+−+−) followed by a commensurate ferrimagnetic-like phase (+ + −) for temperatures from 85 to 96.5 K and then by an incommensurate longitudinal spin wave (ICLSW) between 96.5 K and the critical temperature T N = 138 K [15] (in the previous papers [12,16,17] a direct zero-field phase transition from AFI to ICLWS phases was observed). The effect of the field is to extend the region of the ferrimagnetic phase, which is the only ordered phase for H > 9 T. Thus, the ANNNI model and its extensions have been proposed [11,12,[18][19][20] as relevant to explain the experimental data observed in the material of interest.…”
Section: Introductionmentioning
confidence: 99%